Non‐A non‐B aortic dissection: A literature review. Issue 5 (5th February 2021) - Howard, Callum; Ponnapalli, Anuradha; Shaikh, Safwan; Idhrees, Mohammed; Bashir, Mohammad
Abstract: Non‐A non‐B aortic dissections are an infrequent occurrence and represent a small proportion of aortic dissections. Treating this life‐threatening medical emergency often requires surgeons to undertake some one of the most challenging surgical or endovascular cases in medicine. This literature review aims to define and classify non‐A non‐B dissections, describe their epidemiology as well as their pathology. This review also aims to discuss the range of surgical techniques employed in their treatment and management and to investigate the patient outcomes associated with each technique.